Behavioral Willingness, Descriptive Normative Perceptions, and Prescription Stimulant Misuse among Young Adults 18-20. (28th January 2022) - Fossos-Wong, Nicole; Litt, Dana M.; King, Kevin M.; Kilmer, Jason R.; Fairlie, Anne M.; Larimer, Mary E.; Lee, Christine M.; Geisner, Irene M.; Cimini, M. Dolores; Lewis, Melissa A.
ABSTRACT: Objective: It is critical to gain further understanding of etiologic factors, such as descriptive normative perceptions and behavioral willingness, that are associated with prescription stimulant misuse (PSM) among young adults. Our primary hypotheses were that descriptive normative perceptions for PSM (i.e., perceptions of how much and how often others engage in PSM) and perceived peer willingness (i.e., perceptions of how open others are to PSM under certain circumstances) would be positively associated with higher willingness to engage in PSM, which in turn would account for significant shared variance with self-reported PSM. Method: Data were collected from a U.S. sample of 18–20-year-olds (N = 1, 065; 54.5% females; 70.5% White) recruited for a larger study on alcohol-related risky sexual behavior. Results: Findings indicated higher descriptive normative perceptions and higher perceived peer willingness were associated with higher participants' willingness to engage in PSM. Participants' own willingness was positively associated with PSM. Finally, participants' own willingness to use, descriptive normative perceptions, and perceived peer willingness were associated with higher willingness to engage in PSM, which accounted for significant shared variance with self-reported PSM. Conclusions: Findings suggest the potential utility of personalized feedback interventions for PSM that focus on constructs such as descriptive normative perceptions and behavioral willingness.